Mathematical Analysis of Microstrip Diplexer Design for WLAN System - S. Mezaal, Yaqeen; K. Khaleel, Shahad (International Journal of Engineering and Technology, 2018)
Miniature microstrip diplexer at band frequencies of (1.45/1.95GHz and 2.5/3.5GHz) in two considered channels using the coupled stepped impedance resonators (SIRs) has been presented in this study with mathematical analysis. This diplexer has dual pairs of coupled SIRs with impedance ratioÂ and the source-load coupling lines. As a result of the tuning of impedance ratio and length ratio Â of SIRs, the resonant modes are possibly determined to achieve 2nd order bandpass filter (BPF) with dualband frequency responses for the investigated diplexer. The investigated microstrip diplexer has a simple outline, compact dimensions, an in effect design technique and straightforward calculations of impedance, electrical lengths, fractional bandwidth, coupling factors and other electrical specifications.